1997
DOI: 10.1080/00102209708935609
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Destruction of Chlorinated Hydrocarbons by Reductive Pyrolysis∗

Abstract: A rigorous thesmochemical analysis of the pyrolysis of aromatic chlorides shows that destruction efficiencies in excess of 99.999 percent are possible in a reducing atmosphere at temperatures near 1000 K. This process used for the destruction of chlorinated organic om pounds yields non-halogenated hydrocarbons and hydrochloric acid as reaction products. Qualitative batch experiments on chloromethane and polychlorinated biphenyls (PCBs) showed that such efficiencies could be obtained in residence times below 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Volatilization of iodine from the melter to the MOG system depends on how much iodine might be incorporated in the glass, into particulate matter in the off-gas system (that is eventually captured in scrubber effluents or in particulate filters), and how much is volatilized, forming gaseous species such as I 2 , ICl, HI, HOI, and organic iodides. Because of the relatively high temperatures and estimated low affinity of glass for iodine, it is conservative to assume that, like municipal waste incinerators, inorganic and organic iodides and other halides evolve to the off-gas (Wang et al 2007;Wikström and Marklund 2000) or from pyrolysis (Barton and Mordy 1984;Grossi et al 2007;Hall and Williams 2006;Ravindran et al 1997;Yang et al 2013).…”
Section: Glass Meltermentioning
confidence: 99%
“…Volatilization of iodine from the melter to the MOG system depends on how much iodine might be incorporated in the glass, into particulate matter in the off-gas system (that is eventually captured in scrubber effluents or in particulate filters), and how much is volatilized, forming gaseous species such as I 2 , ICl, HI, HOI, and organic iodides. Because of the relatively high temperatures and estimated low affinity of glass for iodine, it is conservative to assume that, like municipal waste incinerators, inorganic and organic iodides and other halides evolve to the off-gas (Wang et al 2007;Wikström and Marklund 2000) or from pyrolysis (Barton and Mordy 1984;Grossi et al 2007;Hall and Williams 2006;Ravindran et al 1997;Yang et al 2013).…”
Section: Glass Meltermentioning
confidence: 99%
“…DDT and hexachlorobenzene, and of certain non-chlorinated hydrocarbons such as cellulose and lignin, which are in principle the main source of precursors in MSW. PCBs and chlorinated pesticides, present in high concentrations in the waste input of the RKI, require longer residence times at elevated temperatures for decomposition than cellulose and lignin [17][18] because the carbon-chlorine bond is much stronger than the carbon-carbon bond. So it is to be expected that in waste incinerators cellulose and lignin are completely thermally destroyed in the furnace and do not yield PCDD/F precursors in the combustion gas.…”
Section: Resultsmentioning
confidence: 99%
“…Barat and Bozzelli 14 showed that an overall reaction of the form 15 have shown from thermodynamic arguments that a similar dechlorination in hydrocarbon-rich environments is also possible. These observations suggest that dechlorination may occur under the correct conditions, conditions that may be possible in a microwave plasma.…”
Section: Microwave Technology For Waste Treatmentmentioning
confidence: 99%